THE RIGHT OF A MINOR PERSON TO LEGAL ASSISTANCE AND EXERCISE OF THIS RIGHT - KONDRATIEVA, LYUDMYLA (Ehrlich’s Journal, 2025)
The article is devoted to the right of a minor to legal aid, which is enshrined directly in Article 59 of the Constitution of Ukraine. Based on the analysis of regulatory legal acts of the legislation of Ukraine, the author emphasizes that the state guarantees compliance with this right, establishes legislative procedures for its implementation, in particular, obliges state apparatus bodies and officials to respond to violations of this right within the time limits established by law and take urgent measures that will help prevent violations of the rights of minors, especially in family legal relations. According to the author of the article, a necessary condition for a minor to exercise his rights, freedoms and interests in any legal relations is the state’s guarantee of obtaining professional legal aid from a lawyer, because life situations in which a minor may find himself require compliance with current legislation, and ignorance of it can lead to negative consequences. The lack of special legal knowledge should be compensated by the professional assistance of a lawyer. The article notes that professional legal assistance by a lawyer in court exists in the form of judicial (civil procedural representation). In this case, a minor is not deprived of the right to participate in the process of considering and resolving a case concerning him in court. At the same time, the author of the article distinguishes between the concepts of “providing professional legal assistance” and “representation of a person in court”, which are not identical, since they imply a different subject composition. Thus, according to the current legislation, lawyers can provide professional legal assistance, while procedural representation is carried out by legal representatives, attorneys or any other persons defined by law in certain legal relations. The author shares the opinion of scholars-specialists in civil procedure that the right to legal assistance by a lawyer should be regarded as a procedural, not a substantive right. As a result, the conclusion is made that the implementation of the right to legal assistance is based on compliance with the principles of equality of all before the law and the court and the absence of discrimination on the basis of a person’s age.